Designing Educational Games With Fisher Yates Shuffle Method In Early Childhood at TKIT Al Muqorrobin Based On Android - Haryanto, Yuli (Cattleya Darmaya Fortuna, 2023)
Designing educational games with the Fisher Yates Shuffle method in early childhood at TKIT Al Muqorrobin based on android. The Fisher Yates Shuffle method is an algorithm for generating random permutations and one of the most prominent randomization techniques used in creating apps so that users don't get bored when the problem comes out the same pattern. With the creation of an Educational Game with the Fisher Yates Shuffle Method in Early Childhood at TKIT Al Muqorrobin based on Android. In this application, educational games can be used easily. This Early Childhood Education Game at TKIT Al Muqorrobin is made with Android Studio and Java platforms as its programming languages. This application can be used to make it easier for educators to teach letter recognition. Finally, with the Fisher Yates Shuffle method Educational Game in Early Childhood based on Android, students are happy with the new learning method.